Cooperation of Enterprises of the Sector of Food Processing Industry with the Entities Rendering Business Services - Robert Nowacki; Katarzyna Wasilik (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
An intensive competition in the sector of food processing industry sets forth the requirement of improving the processes of operating in the market. One of them is cooperation with the entities rendering business services. The aim of the paper is to analyse the level of making use of business services by the enterprises operating in the food processing industry as well as to assess the cooperation between the companies rendering such services. The authors used for this purpose the results of quantitative research carried out among the enterprises operating in the polish market. In result of thereof they have ascertained that, in general, along with the growth of the size of an enterprise there grows the scale of the use of business services, and it must be said that greater propensity to use business services is displayed by the enterprises with the share of foreign capital. At the same time, the assessment of cooperation with the companies rendering business services is not determined either by the size of an enterprise or by the share of foreign capital.